Cultural Awareness in Afro-Costa Rican Education 1: A Literature Review - Chinchilla Jiménez, María Daniela (2025)
This study analyzed the factors contributing to the cultural disconnection of the Afro-descendant population in Costa Rica, focusing on the socio-educational, cultural, and economic dimensions that influenced their integration. It emphasized the role of education as a system that historically conditioned the development, integration, and preservation of Limón Creole identity, limiting its contribution to Costa Rican identity. Through a critical analysis, the research revealed how historical and institutional policies perpetuated a “linguistic apartheid,” relegating the Creole language and its speakers to a secondary status in the national sociopolitical narrative. Based on Lemus (2018), the study underscored the role of language as a primary medium for cultural transmission and group identity. The neglect of Limón Creole in governmental policies led to cultural and linguistic alienation, placing its speakers in a sociocultural limbo. This study also examined the broader implications of linguistic diversity within the Costa Rican educational system, proposing strategies to revalue Afro-descendant linguistic and cultural heritage. By advocating for the inclusion of the Creole language in Costa Rican educational policies, it sought to counteract its historical devaluation and promote its recognition as a vital component of national identity, fostering a more inclusive understanding of Costa Rican cultural diversity.